Semantic and Syntactic Aspects of “Bāyestan” in Tārīkh-i Bayhaqī - Mona Valipour (مطالعات زبانی و بلاغی)
Syntactic and semantic analysis of modal verbs, particularly “bāyestan”, has been a challenging topic in Persian language studies due to its special inflectional, syntactic, and semantic states. These studies are mainly focused on the uses of this verb in contemporary Persian, ignoring the historical texts. The current study, relying on data derived from Tārīkh-i Bayhaqī (1,114 cases), aims to review the challenging semantic and syntactic aspects of this verb. First, by referring to some of the morphosyntactic features of this verb, we have identified its status in terms of tense, time implications, and differentiation between different forms of past and present tenses. Next, we have shown that in the valency of this verb there is either a noun phrase (subject) or a complement clause. Subsequently, we have introduced and discussed two assumptions about the verb bāyestan: either considering the complement clause as the subject and the expletive pro. We have thus shown that the impersonality of this verb is due to the syntactic and semantic nature of the subject and has nothing to do with the changes of the verb during the grammaticalization. Afterward, it was found that non-finite clauses have no syntactic subject, and what has been suggested in some research as the 'subject' of “Ra” is in fact a noun phrase whose syntactic role is the optional complement of the verb bāyestan and its semantic role is the beneficiary. This noun phrase is essentially independent of the complement clause. In this regard, it was found that unlike Davari's analysis (1394), modality in non-finite clauses may also be agent-oriented, and at least based on Tārīkh-i Bayhaqī data, it is not possible to consider moving from action-oriented modality to agent-oriented modality as a grammaticalization process. Finally, the semantic examination of the verb bāyestan supported the previous analyses in this field and revealed that all uses of the verb in the Tārīkh-i Bayhaqī are non-epistemic modality.